(untitled) (Medical Forum Monthly, 2024)
Objective: In a tertiary care hospital in Karachi, Pakistan, this research sought to determine how well the Mehran Risk Score predicted CIN in patients having coronary angiography. Study Design: a prospective single-arm cohort study. Place and Duration of Study: This study was conducted at the Department of Adult Cardiology, National Institute of Cardiovascular Disease, Karachi from September 16, 2019, and ending on March 15, 2020. Methods: At the National Institute of Cardiovascular Disease (NICVD), a descriptive cross-sectional research was carried out. Informed permission was acquired before patients who met the inclusion criteria were enrolled. Serum creatinine levels were tested 48 and 72 hours before and after the surgery. For every patient, the Mehran Score was determined, and the CIN was noted. Results: 230 individuals with a mean age of 57.56 ± 15.45 years and a mean Mehran Score of 4.84 ± 1.98 were included in the research. Of them, 64 (27.8%) had CIN, and 150 (65.2%) were men. The ROC analysis yielded an area under the curve (AUC) of 0.9296, and a threshold score of > 5.50 indicated strong prediction accuracy. Conclusion: When patients with acute coronary syndrome undergo coronary angiography, the Mehran Risk Score provides useful differentiation between risk groups and accurately predicts the development of CIN. To further corroborate these results, bigger cohort studies are required in the future.